A alienação judicial da integralidade de imóveis indivisíveis e seus reflexos frente ao direito de propriedade dos condôminos alheios a execução - Tibolla, Rafael (2024)
This study addresses a relevant topic that concerns the judicial alienation of the entirety of indivisible properties in a common condominium situation, as opposed to the rights of condominium owners who are not part of the process that gave rise to the expropriation act, an important matter as it relates to to the fundamental right relating to private property. On the one hand, based on article 843 of the current Code of Civil Procedure, there are court decisions considering the possibility, in any case, of judicial alienation of the entirety of indivisible properties, only protecting co-owners the right of preference in the acquisition of the property or the equivalent in money from your share in the property. However, it is necessary to carefully analyze the lack of concern that such decisions have given to preserving the right to private property of the owners of the property under lien who are not responsible for paying the debt in execution, and such decisions must be analyzed from all aspects, as, Judicial sales involving the entirety of properties under a common condominium regime, in certain situations, may represent an affront to the right to free disposal of assets by co-owners of indivisible properties who are not defendants in the execution. Thus, based on doctrinal, jurisprudential and legislative studies related to the topic, the objective of this work is to reflect on the consequences arising from judicial alienations of the entirety of indivisible properties in a condominium situation, as a possible affront to the private property right of other condominium owners not enforced, a fundamental right guaranteed by the 1988 Constitutional Charter.